Young (<35 years) haploidentical versus old (≥35 years) mismatched unrelated donors and vice versa for allogeneic stem cell transplantation with post-transplant cyclophosphamide in patients with acute myeloid leukemia in first remission: a study on behalf of the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Nagler, Arnon; Labopin, Myriam; Swoboda, Ryszard; Blaise, Didier; Angelucci, Emanuele; Vydra, Jan; Corral, Lucía López; Bramanti, Stefania; Chiusolo, Patrizia; Kwon, Mi; Koc, Yener; Itäla-Remes, Maija; et al. (Bone marrow transplantation, 2024)
We compared transplantation (HSCT) outcomes in AML patients undergoing HSCT with post-transplant cyclophosphamide (PTCy) in first complete remission from 1065 young (<35 years) haploidentical (Haplo) donors (yHaplo) vs. 147 old (≥35 years) mismatched unrelated donors (oMMUD) (first comparison) and from 271 young (<35 years) MMUD (yMMUD) vs. 1315 old (≥35 years) Haplo donors (oHaplo) (second comparison). Acute graft-versus-host disease (aGVHD) grades II-IV were significantly lower in the yHaplo vs. oMMUD group (HR = 0.62, p = 0.007). There were no significant differences in chronic GVHD, non-relapse mortality (NRM), relapse incidence, leukemia-free survival, overall survival, and GVHD-free and relapse-free survival. As for the second comparison, more patients in the oHaplo group had de novo AML, 86.6% vs. 81.9% in the yMMUD group (p = 0.044), while myeloablative conditioning was used more frequently in the yMMUD group, 53.3% vs. 46.8% in the oHaplo group (p = 0.049). aGVHD grades II-IV and NRM were significantly lower in the yMMUD vs. oHaplo group (HR = 0.69, p = 0.013 and HR = 0.60, p = 0.022). All other transplant outcomes did not differ. In conclusion, HSCT from young alternative donors (<35 years) results in a lower incidence of grades II-IV aGVHD. In addition, NRM is lower in HSCT from yMMUD compared to HSCT from oHaplo.
Keywords: Transplantation, Haploidentical; Adolescent; Europe; Adult; transplantace hematopoetických kmenových buněk; Male; Leukemia, Myeloid, Acute; lidé; Hematopoietic Stem Cell Transplantation; lidé středního věku; přežití bez známek nemoci; akutní myeloidní leukemie; Humans; Graft vs Host Disease; nepříbuzný dárce; Disease-Free Survival; Age Factors; Child; Evropa; Middle Aged; věkové faktory; homologní transplantace; Young Adult; haploidentická transplantace; Cyclophosphamide; Remission Induction; Transplantation Conditioning; indukce remise; cyklofosfamid; Unrelated Donors; mužské pohlaví; příprava pacienta k transplantaci; nemoc štěpu proti hostiteli; dospělí; Transplantation, Homologous; mladý dospělý; dítě; ženské pohlaví; mladiství; Female